2004
DOI: 10.1269/jrr.45.89
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Prior Low-dose X-ray Irradiation on Carbon Tetrachloride-induced Hepatopathy in Acatalasemic Mice

Abstract: The catalase activities in blood and organs of the acatalasemic (C3H/AnLCs(b)Cs(b)) mouse of C3H strain are lower than those of the normal (C3H/AnLCs (a)Cs(a)) mouse. We examined the effects of prior low-dose (0.5 Gy) X-ray irradiation, which reduced the oxidative damage under carbon tetrachloride-induced hepatopathy in the acatalasemic or normal mice. The acatalasemic mice showed a significantly lower catalase activity and a significantly higher glutathione peroxidase activity compared with those in the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…These results were consistent with the results in our previous reports [17,18]. Taken together, these findings suggest that radon inhalation has a similar biological effect to that of low-dose X-irradiation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results were consistent with the results in our previous reports [17,18]. Taken together, these findings suggest that radon inhalation has a similar biological effect to that of low-dose X-irradiation.…”
Section: Discussionsupporting
confidence: 93%
“…These findings indicate that the free radical accumulation induced by the lack of catalase and the administration of CCl 4 is more completely neutralized by high GPx activity and low-dose irradiation in acatalasemic mice [17]. We also reported that the effects of post-treatment with low-dose (0.5 Gy) X-irradiation reduced the oxidative damage associated with CCl 4 -induced hepatopathy in acatalasemic mice.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Low-dose X-or γ-irradiation activates antioxidative functions in some organs and, consequently, inhibits oxidative injury [8][9][10][11][12][13]. In mice for example, pretreatment with low-dose X-irradiation inhibits carbon tetrachloride (CCl 4 )-induced hepatopathy [8] and treatment with low-dose (0.5 Gy) X-irradiation following exposure to CCl 4 reduced the oxidative damage associated with CCl 4 -induced hepatopathy. [9].…”
Section: Introductionmentioning
confidence: 99%